Two new species of Promonhystera Wieser, 1956 (Nematoda: Monhysterida: Xyalidae) from the South China Sea - Huang, Mian; Xu, Kuidong (Zootaxa, 2024)
Two new species of free-living marine nematodes from the littoral sediment of the South China Sea are described as Promonhystera papilla sp. nov. and Promonhystera fluctispicula sp. nov. Both new species are characterized by striated cuticle; circular amphideal fovea; anterior sensilla in two circles, inner labial sensilla setiform; funnel-shaped buccal cavity; elongated spicules and conico-cylindrical tail. P. papilla sp. nov. is different from all known species of the genus by longer body length (more than 2.1mm versus less than 1.5 mm in other species), longer spicules (sp/a.b.d. = 4.1–4.6 versus ≤ 2.7) and males with three papilliform precloacal supplements and one small postcloacal papilla (versus absence) and gubernaculum boot-shaped. P. fluctispicula sp. nov. is similar to P. tricuspidata Wieser, 1956 in having similar waved spicules but differs from the latter species by tail conico-cylindrical (versus conical) and simple plate-like gubernaculum without tooth (versus gubernaculum with four distal teeth).